Striving for achievement in a new era: China debates its global role - Wei, Ling (Pacific review, 2020)
Since the doctrine of 'keeping a low profile (KLP), attaining some achievement (ASA)' was developed, there has been much attention and study of the KLP, but little discussion of the ASA. However, it is exactly how the ASA has been observed that can well reflect Chinese perception of its global role. In the paper, the ASA is treated as a continuum or a fluid concept with changing values. There have been significant adjustments in the official expression of the ASA doctrine since the 2008 global financial crisis, from the original 'attaining some achievement' to 'proactively attaining achievement' around 2011, 'striving for achievement' in 2013, and 'striving for achievement in a new era' in 2017. Along with these changes, there have been roughly three rounds of debates on the ASA among Chinese scholars. While they generally agree on more proactive diplomacy in attaining achievement, scholars have debated on what achievements to attain and how to attain these achievements. While the ultimate goal is defined officially as Chinese rejuvenation, specific and interim goals of 'striving for achievement' in scholarly debates have targeted mainly China's strategic capability, institutional power and normative power. Chinese scholars have also debated on the general principles, diplomatic style and tactics that China should follow by focusing on three relationships: the relationship between the KLP and the ASA, the Sino-US relationship, and the relationship between China and the international system. The author provides an analytical framework and thorough examination of the development of the ASA doctrine, and presents the scholarly debates along its development path, in the hope that this study may facilitate the understanding of the outside world on how China perceives its global role.